2015
DOI: 10.1096/fj.14-261453
|View full text |Cite
|
Sign up to set email alerts
|

FE65 and FE65L1 amyloid precursor protein‐binding protein compound null mice display adult‐onset cataract and muscle weakness

Abstract: FE65 and FE65L1 are cytoplasmic adaptor proteins that bind a variety of proteins, including the amyloid precursor protein, and that mediate the assembly of multimolecular complexes. We previously reported that FE65/FE65L1 double knockout (DKO) mice display disorganized laminin in meningeal fibroblasts and a cobblestone lissencephaly-like phenotype in the developing cortex. Here, we examined whether loss of FE65 and FE65L1 causes ocular and muscular deficits, 2 phenotypes that frequently accompany cobblestone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…We observed strong deficits for the FE65/FE65L1-DKO mice in the MWM tasks. Since interpretation of the cognitive deficits observed for these mice is confounded by altered anxiety, activity and possibly visual abilities 16 the analyzed data are not further discussed, but are presented in Supplementary Fig. S1 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed strong deficits for the FE65/FE65L1-DKO mice in the MWM tasks. Since interpretation of the cognitive deficits observed for these mice is confounded by altered anxiety, activity and possibly visual abilities 16 the analyzed data are not further discussed, but are presented in Supplementary Fig. S1 .…”
Section: Resultsmentioning
confidence: 99%
“…Yet, only FE65/FE65L1-DKO mice showed deficits in the maintenance phase of LTP and only FE65-KO mice showed a trend towards PTP deficits. A subset of aged FE65L1 KO mice (16–20 months old) demonstrated cataract and corneal ulcerations 16 . Thus, we cannot formally exclude the possibility that younger FE65L1 KO mice have some visual acuity deficit that interferes with their performance in the MWM tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, memory deficits were observed in the MWM test for the FE65 KO (lacking both p60 and p97 isoforms) and FE65L1 KO mice in our study (Strecker et al, 2016). Confounding behaviors for locomotion analyses and possible loss of vision in FE65/FE65L1 DKO mice (Suh et al, 2015; Strecker et al, 2016) made it impossible to interpret the MWM spatial learning deficits observed for FE65/FE65L1 DKO mice.…”
Section: Fe65/fe65l1 Mutant Micementioning
confidence: 99%
“…These are aggravated in FE65/FE65L1 DKO compared to FE65 or FE65L1 KO mice NMJs (Strecker et al, 2016), possibly leading to muscle degeneration/denervation (Suh et al, 2015) and the locomotion deficits and impairments in strength observed in these mice (Strecker et al, 2016). …”
Section: Fe65/fe65l1 Mutant Micementioning
confidence: 99%